FEASIBILITY EVALUATION OF HEAVY EQUIPMENT RENTAL INVESTMENT IN SOUTH KALIMANTAN - Purwantoro, Almuntofa; Wibowo, Guswiem; Lendra, Lendra (Universitas Islam Nahdlatul Ulama Jepara, 2024)
Development in the construction sector in Indonesia is one of the reasons investment is why heavy equipment has increased, but in 2020 Indonesia's economic growth contracted by 2.07 due to Covid-19. Economic growth in Indonesia in 2020 affected heavy equipment rental companies, especially in South Kalimantan. To assess the feasibility of investments that have been carried out in this study, one of them relies on the analysis of the investment break-even point and its sensitivity. The evaluation aims to determine the feasibility of the business that has been implemented. Based on Break Even Point that occurred at 2.46 years at that time revenue amounted to Rp. 98,784,716,825. The results of the sensitivity analysis stated that the assumption of fixed income and expenditure costs increased by 50% resulting in an NPV of Rp. 67,126,506,911 declared feasible, the break-even point obtained at 4.50 years or 4 years 163 days of income of Rp. 67,126,506,911. Revenue decreased by 50% and fixed expenses resulted in an NPV of -Rp. 24,104,127,174 declared unfeasible, the break-even point did not find results because the company still suffered losses until 2026. Revenue fell by 50% and income increased by 50% resulting in NPV -Rp. 100,720,629,289 declared unfeasible, the break-even point did not find results because the company was still experiencing losses until 2026.EVALUASI KELAYAKAN INVESTASI PENYEWAAN ALAT BERAT DI KALIMANTAN SELATANPembangunan di bidang konstruksi di Indonesia menjadi salah satu alasan investasi mengapa peralatan alat berat mengalami peningkatan namun pada tahun 2020 pertumbuhan ekonomi Indonesia mengalami kontraksi sebesar 2,07 akibat covid-19. Pertumbuhan ekonomi di Indonesia pada tahun 2020 berimbas perusahaan penyewaan alat berat khususnya di Kalimantan Selatan. Untuk menilai kelayakan investasi yang telah dilaksanakan dalam penelitian ini salah satunya bergantung pada analisis break even point inventasi dan sensitivitasnya. Evaluasi tersebut dimaksud bertujuan untuk mengetahui kelayakan usaha yang telah di laksanakan. Berdasarkan Break Even Point terjadi pada 2,46 Tahun pada saat itu pendapatan sebesar Rp. 98.784.716.825. Hasil analisis sensitivitas menyatakan bahwa asumsi pemasukan tetap dan biaya pengeluaran naik 50% menghasilkan NPV yaitu Rp. 67.126.506.911 dinyatakan layak, titik impas mendapatkan pada 4,50 tahun atau 4 tahun 163 hari pendapatan sebesar Rp. 67.126.506.911. Pemasukan turun 50% dan biaya pengeluaran tetap menghasilkan NPV yaitu -Rp. 24.104.127.174 dinyatakan tidak layak, titik impas tidak menemukan hasil karena perusahaan masih mengalami kerugian sampai tahun 2026. Pemasukan turun 50% dan pemasukan naik 50% menghasilkan NPV -Rp. 100.720.629.289 dinyatakan tidak layak, titik impas tidak menemukan hasil karena perusahaan masih mengalami kerugian sampai tahun 2026.